NARRATIVE FUNCTION OF THE APOCALYPSE - Jang, Young (Scriptura, 2002)
Apocalyptic stories, as rhetorical-symbolic narratives, urge the hearer to view his/her historical situation afresh and to act accordingly. To find out how this happens, the transforming power of the Apocalypse has been analysed according to two contexts: the literary and the socio-historical. Through his apocalyptic narrative, John wants to illumine the reality behind the context of the audience and to transform them into a Christian community with a shared vision and conviction. In a broad sense, the book is concerned with the author’s understanding of God (narrative theology), and how it can be related to the audience’s response (narrative function). From this study of the rhetorical function of the book, we may conclude that John tries to persuade the evildoers to repent and the faithful to remain witnesses in the world